The moral conflict of law and neuroscience - Alces, Peter A. (The University of Chicago Press, 2018)
"New insights offered by neuroscience have provoked discussions of the nature of human agency and responsibility. Alces draws on neuroscience to explore the internal contradictions of legal doctrines, and consider what would be involved in constructing novel legal regimes based on emerging understandings of human capacities and characteristics not only in criminal law but in contract and tort law."--Provided by publisher.